2020
DOI: 10.1021/acschemneuro.0c00479
|View full text |Cite
|
Sign up to set email alerts
|

ATP Kinetically Modulates Pathogenic Tau Fibrillations

Abstract: Advanced understanding of Alzheimer's disease (AD) and several tauopathies over the past decades indicates the pathological importance of tau aggregation in these diseases. Herein, we demonstrated that adenosine triphosphate (ATP), a highly charged anionic molecule abundant in the cytosol of cells, catalyses tau fibrillation via supramolecular complexation with basic residues of tau. Our results showed that ATP attracts multiple lysine residues of four-repeat domain of tau (K18), thereby immediately forming di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 67 publications
2
19
0
Order By: Relevance
“…High levels of Zn 2+ were found in cell damage or neurodegenerative conditions [28] . What is more, ATP in the 0.1–10 mM concentration range have been recently reported to kinetically modulate pathogenic tau fibrillation [68] . Furthermore, millimolar concentrations of ATP were found to be linked to a reduction of the fibrillation of neuronal proteins [69] and ATP was found to specifically bind the RNA-binding domain of the nucleocapsid protein of SARS-CoV-2 with a millimolar K D [70] .…”
Section: Discussionmentioning
confidence: 99%
“…High levels of Zn 2+ were found in cell damage or neurodegenerative conditions [28] . What is more, ATP in the 0.1–10 mM concentration range have been recently reported to kinetically modulate pathogenic tau fibrillation [68] . Furthermore, millimolar concentrations of ATP were found to be linked to a reduction of the fibrillation of neuronal proteins [69] and ATP was found to specifically bind the RNA-binding domain of the nucleocapsid protein of SARS-CoV-2 with a millimolar K D [70] .…”
Section: Discussionmentioning
confidence: 99%
“…Phase-separated tau forms droplets that serve as intermediates toward aggregation [ 29 ]. Physiological concentrations of ATP at 0.1–10 mM enhanced the fibrillation of 10 μM tau K18 (equivalent to 10–1000-fold molar ratio) by accelerating aggregation in a concentration-dependent manner [ 54 ] through energy-independent binding to tau proteins [ 55 ]. It may seem paradoxical that ATP would enhance the formation of amyloids and prions that are associated with diseases.…”
Section: Atp Regulates Biomolecular Condensatesmentioning
confidence: 99%
“…A significant increase in the average fluorescence intensity of tau-BiFC by 60-70% in both HEK293 and SH-SY5Y cells indicates an enhanced intracellular tau aggregation with upregulation of ATP. 84 Recent studies have also shown that O-linked β-N-acetylglucosamine (O-GlcNAc) reduces tau hyperphosphorylation by protecting the tau phosphorylation sites in normal brain. In pathological condition, tau is de-glycosylated and becomes a substrate for kinases.…”
Section: Split-venus Bifc (Fluorescence Turn-on Biosensor)mentioning
confidence: 99%
“…Cells expressing tau‐BiFC biosensor are also used to study tau aggregation in ATP dyshomeostasis. 84 To examine whether an increased level of ATP affects the extent of tau self‐assembly, the tau‐BiFC biosensor cells are treated with TNFα/CHX to induce an increase in the intracellular ATP levels. A significant increase in the average fluorescence intensity of tau‐BiFC by 60–70% in both HEK293 and SH‐SY5Y cells indicates an enhanced intracellular tau aggregation with upregulation of ATP.…”
Section: Split Fluorescent Protein Complementation or Bifc ‐Based Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation